2020
DOI: 10.1093/eurheartj/ehaa209
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean diet, plasma metabolome, and cardiovascular disease risk

Abstract: Aims To investigate whether metabolic signature composed of multiple plasma metabolites can be used to characterize adherence and metabolic response to the Mediterranean diet and whether such a metabolic signature is associated with cardiovascular disease (CVD) risk. Methods and results Our primary study cohort included 1859 participants from the Spanish PREDIMED trial, and validation cohorts included 6868 participants from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(136 citation statements)
references
References 45 publications
5
115
0
Order By: Relevance
“…Our results highlighting the changes in plasma metabolites related to lipid metabolism are in line with other studies [20,26]. A recent investigation that identified a metabolic signature of adherence to the MedDiet showed that out of 67 metabolites, 45 were lipids followed by 19 amino acids, 2 vitamins and 1 xenobiotic [26]. Although we used a different methodology and a different set of biomarkers, and thus we could not replicate this metabolic signature, our results support that the MedDiet may induce changes in relevant lipid species and subclasses related to atherogenic risk.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results highlighting the changes in plasma metabolites related to lipid metabolism are in line with other studies [20,26]. A recent investigation that identified a metabolic signature of adherence to the MedDiet showed that out of 67 metabolites, 45 were lipids followed by 19 amino acids, 2 vitamins and 1 xenobiotic [26]. Although we used a different methodology and a different set of biomarkers, and thus we could not replicate this metabolic signature, our results support that the MedDiet may induce changes in relevant lipid species and subclasses related to atherogenic risk.…”
Section: Discussionsupporting
confidence: 93%
“…Our results highlighting the changes in plasma metabolites related to lipid metabolism are in line with other studies [20,26]. A recent investigation that identified a metabolic signature of adherence to the MedDiet showed that out of 67 metabolites, 45 were lipids followed by 19 amino acids, 2 vitamins and 1 xenobiotic [26].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Data on the relationships between NCDs and dairy foods and eggs are less consistent but overall indicate possible harm at very high intakes [ 28 , 30 ]. Moreover, the PREDIMED (Primary Prevention of Cardiovascular Disease with Mediterranean Diet) trial has shown that the implementation of a diet resembling the traditional Mediterranean diet, in many ways similar to the dietary pattern proposed by the Eat–Lancet Commission, substantially reduces the incidence of cardiovascular diseases and diabetes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%